Implementation of the FAST Fast Corner Detection Algorithm (Feature Form Accelerated Segment Test) and Augmented Reality to Determine the Authenticity of Batik Case Study (Batik Trusmi) Cirebon - Dadan Ramdoni; Tito Sugiharto; Aji Permana; Rika Nugraha (Universitas Kuningan, 2019)
AbstractIndonesia has a diversity of cultural arts, including art crafts. This craft art covers several fields including the arts of wood crafts, metal crafts, ceramic crafts, leather crafts, and textile crafts. In textile crafts, there are several types, such as weaving, knitting, embroidery, and batik. One area that has a characteristic of batik is Cirebon. Cirebon has a traditional batik center, namely Trusmi Batik. TrusmiBatik is a company that produces various kinds of batik, including mega mendungbatik motifs, paksinagaliman, patrankeris, patran kale, umbrella lion, barong lion, sunyaragian arum garden, banjarbalong, ayam alas, supiturang, nagaseba, sawat bride and groom cymbals, etc. The Trusmi batik company has problems on how to minimize artificial batik and how to distinguish original batik from artificial batik. One of technologiesthat can be used is Augmented Reality by using a QR Code (Quick Response) as a sign especially those which can find out whether the batik is original or imitation. The Feature From Accelerated Segment Test is a high-speed interest point detection algorithm based on pixel considerations in circular areas around interest points. Using the FAST algorithm can be used to detect markers so that they can distinguish original batik from artificial batik.Keywords: Trusmi Batik, QR Code, Augmented Reality, FAST.